Biological agents targeting interleukin-13 for atopic dermatitis. (4th May 2022) - Chiricozzi, Andrea; Gori, Niccolò; Maurelli, Martina; Gisondi, Paolo; Caldarola, Giacomo; De Simone, Clara; Peris, Ketty; Girolomoni, Giampiero
ABSTRACT: Introduction: Atopic dermatitis (AD) is a chronic inflammatory skin disease that is pathogenically driven by type-2 inflammation. Interleukin-13 (IL-13) plays a central role in AD pathogenesis, as confirmed by the clinical efficacy of agents that selectively block IL-13, although their therapeutic value and place-in-therapy are incompletely defined. Areas covered: This review article aimed to describe preclinical and clinical data regarding selective IL-13 inhibitors investigated in AD. In particular, we discuss the clinical outcomes obtained with lebrikizumab and tralokinumab, which are in a more advanced phase of development. Expert opinion: Biological agents that neutralize IL-13 have demonstrated clinical benefits in treating AD with excellent safety profiles. Robust clinical evidence exists in support of tralokinumab, which underwent phase III trials, met the predefined primary endpoints, and is approaching the market. In contrast, clinical trial testing for lebrikizumab needs to be completed to fully assess its therapeutic potential. PLAIN LANGUAGE SUMMARY: Selective interleukin-13 (IL-13) inhibitors have shown clinical efficacy against AD, suggesting that IL-13 plays a central in AD pathogenesis. However, the therapeutic value and place-in-therapy of IL-13 inhibitors are not fully defined. This review articledescribed strengths and limitations of different anti-IL-13 agents used to treat AD that might be useful in driving treatment decision.